Rapid detection of nitrite and Listeria monocytogenes in food based on multiple simulated enzyme activities of Fe3O4-ZnO-MnO2 nanocomposites - Shuyang Sun; Wenteng Qiao; Feng Yin; Wei Mi; LuliangWang; Yuhan Jia; Mengjiao Wang; Xinhui Liu; Dacheng Wang; Daotan Liu; Chao Zhao; Xiuling Song; et al. (Food Chemistry: X)
Food safety has emerged as a paramount concern in global health, prompting innovative approaches to ensure the safety of people's sustenance. In this study, a novel strategy was devised to fabricate Fe3O4-ZnO-MnO2 hybrid nanobiocatalysts, which exhibited remarkable enzymatic activity surpassing that of Horseradish peroxidase (HRP) catalysis. It demonstrated exceptional proficiency in decomposing 3,3′,5,5′-tetramethylbenzidine (TMB) without the need for harsh reaction conditions or the aid of H2O2. We established colorimetric detection systems based on Fe3O4-ZnO-MnO2-TMB both for nitrite (NO2−) and Listeria monocytogenes (LM) in food. Impressively, the detection limit of nitrite reached an astonishingly low level of 0.022 mg L−1, and the detection limit for LM was determined to be 3.5 cfu mL−1. These compelling results unequivocally validate the potential of these hybrid nanobiocatalysts to fortify food safety measures. Moreover, they serve as a valuable reference for the colorimetric detection of diverse analytes and the simultaneous detection of multiple targets.